Russia’s Policy in the Field of Climate Change Mitigation - Veselova; D.N. (Дискурс Пи, 2023)
Russia, which is one of the largest emitters of greenhouse gases in the world. In this regard, the position of the Special Presidential Representative on Climate Issues has been introduced, and important documents aimed at mitigation and implementation of appropriate activities are being adopted. The purpose of this article is to review the Russian policy in the field of climate change mitigation and analyze the current trends in this area. The legal and institutional framework for climate policy is characterized. The trends in mitigating the effects of climate change, which are based on ongoing measuresto reduce greenhouse gas emissions, are highlighted. Based on the conducted research, the author comes to the conclusion that the Russian legislation in the field of mitigation is of "soft" nature. There are no penalties or climate taxes. Many regulatory legal acts are approved in violation of the planned deadlines. Not all the identified trends are aimed at reducing greenhouse gas emissions. Thus, constructing carbon polygons and emissionstrading only transfer the carbon footprint from one territory to another. The article notes the slow pace of Russia's transition to "low-carbon rails", which is associated with the energy intensity of the economy. It emphasizes the necessity of using climate-neutral technologies in industry and agriculture to achieve the set goal of ensuring carbon neutrality of the Russian economy by 2060.